THE DEVELOPMENT OF A BELIEF IN SELF-EFFICACY AMONG ADOLESCENTS AGED (12-16) YEARS - Prof. Shaima Nassif Inad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of this research is to define the belief in self-efficacy among adolescents of the ages (12, 14 and 16), as well as to know the significance of differences in the belief in self-efficacy according to the age and gender variables of the subjects of the research sample that reached (150) adolescents by (50) adolescents per year. Each age is divided equally between the sexes. The researcher built a scale (belief in self-efficacy), relying on the theory of planned behavior (Ajzen, 1985), where the scale consisted of (60) items distributed into three domains, and the researcher verified the validity of the scale through apparent validity. The stability of the scale was verified by the re-test method. In analyzing and statistically treating the data, the researcher used several statistical methods, the most important of which are: the T-test for one sample, the analysis of binary variance, and the Pearson correlation coefficient.